Knowledge about sexually transmitted infections in a public school in Huánuco - Cabrera-Solis, Cinddy M. (2019)
Objective: To determine the factors related to the level of knowledge about sexually transmitted infections in public school students Jorge Basadre, Santa María del Valle, Huánuco 2017. Methodology: An observational, analytic, prospective and longitudinal study was carried out. Case design and control. Results: The teacher's performance is not related to the level of knowledge as it was evidenced by a P value (Fisher's test) greater than 0.05, therefore it was not significant. Likewise, it is not a risk factor since an OR of 1.00 was obtained [IC 95% 0.174 - 5.743]. The family structure is not related to the level of knowledge, as it was evidenced a P value greater than 0.05, therefore it was not significant. Likewise, it is not a risk factor since an OR of 0.45 was obtained [IC 95% 0.135 - 1.525]. The motivation of the student is not related to the level of knowledge as it was evidenced had a P value greater than 0.05, therefore it was not significant. Likewise, it is not a risk factor because an OR of 1.00 was obtained [IC 95% 0.088 - 11.422]. Conclusion: The teacher's work performance, student motivation and family dysfunction are not related to the level of knowledge about sexually transmitted infections in students of the Jorge Basadre public school, Santa María del Valle, Huánuco 2017.